Paleo-polyploidization in Lycophytes - Jinpeng Wang; Jigao Yu; Pengchuan Sun; Chao Li; Xiaoming Song; Tianyu Lei; Yuxian Li; Jiaqing Yuan; Sangrong Sun; Hongling Ding; Xueqian Duan; Shaoqi Shen; et al. (Genomics, Proteomics & Bioinformatics, 2020)
Lycophytes and seed plants constitute the typical vascular plants. Lycophytes have been thought to have no paleo-polyploidization although the event is known to be critical for the fast expansion of seed plants. Here, genomic analyses including the homologous gene dot plot analysis detected multiple paleo-polyploidization events, with one occurring approximately 13–15 million years ago (MYA) and another about 125–142 MYA, during the evolution of the genome of Selaginella moellendorffii, a model lycophyte. In addition, comparative analysis of reconstructed ancestral genomes of lycophytes and angiosperms suggested that lycophytes were affected by more paleo-polyploidization events than seed plants. Results from the present genomic analyses indicate that paleo-polyploidization has contributed to the successful establishment of both lineages—lycophytes and seed plants—of vascular plants.